A Critical Analysis of the Australian ECEC Policy Reform: An Opportunity for Transforming Educators into Pedagogical Leaders?. Issue 2 (May 2015) - Loo, Jasmine Kah Yan; Agbenyega, Joseph
THIS PAPER SEEKS TO engage the field of early childhood education and care (ECEC) leadership in critical analysis. Drawing on theorisations from the 'new image of the child', the paper is structured to provide some analytic insight into the implications that current conceptualisations of children have for leadership practices in the field of ECEC. The discussion highlights the need for multi-layered understanding of leadership among ECEC professionals and the importance of leadership for quality ECEC. This paper also identifies and analyses two main issues present in the current Australian ECEC context that appeared to be hindering leadership enactment among ECEC educators. The ultimate intent of this paper is not to critique the existing state of ECEC practice; rather, the value of this work is its potential to intervene in the scholarship of the ECEC transformation and practice, to disrupt dominant practices and highlight the benefits of embracing the explicit and implicit layers of leadership in early childhood pedagogical practices.